Engineering Polysaccharide‐Based Hydrogel Photonic Constructs: From Multiscale Detection to the Biofabrication of Living Optical Fibers. Issue 52 (7th October 2021) - Guimarães, Carlos F.; Ahmed, Rajib; Mataji‐Kojouri, Amideddin; Soto, Fernando; Wang, Jie; Liu, Shiqin; Stoyanova, Tanya; Marques, Alexandra P.; Reis, Rui L.; Demirci, Utkan
Abstract: Solid‐state optics has been the pillar of modern digital age. Integrating soft hydrogel materials with micro/nanooptics could expand the horizons of photonics for bioengineering. Here, wet‐spun multilayer hydrogel fibers are engineered through ionic‐crosslinked natural polysaccharides that serve as multifunctional platforms. The resulting flexible hydrogel structure and reversible crosslinking provide tunable design properties such as adjustable refractive index and fusion splicing. Modulation of the optical readout via physical stimuli, including shape, compression, and multiple optical inputs/outputs is demonstrated. The unique permeability of the hydrogels is also combined with plasmonic nanoparticles for molecular detection of SARS‐CoV‐2 in fiber‐coupled biomedical swabs. A tricoaxial 3D printing nozzle is then employed for the continuous fabrication of living optical fibers. Light interaction with living cells enables the quantification and digitalization of complex biological phenomena such as 3D cancer progression and drug susceptibility. These fibers pave the way for advances in biomaterial‐based photonics and biosensing platforms. Abstract : Polysaccharide‐based, multilayered hydrogel fibers in the photonics arena are explored. Natural ionic‐crosslinking hydrogels are leveraged for developing a hydrogel fiber fusion splicing method and combined with nanoplasmonic‐based photonics for detecting biotargets such as SARS‐CoV‐2. The integration of living entities in the cytocompatible light‐guiding core enables the digitalization and quantification of complex 3D biological events, such as cancer invasive proliferation.